Land suitability modelling using geographical information system (GIS) and multi-criteria decision making (MCDM) - Hussain Khahro, Shabir; Hussain Ali, Tauha; Ali Mangi, Sajjad; Ahmed Memon, Nafees; Hussain Khahro, Qasim (Penerbit UTHM, 2020)
There has been growing concern that the development activities have high potential to cause environmental problems. The decision-makers are trying hard to reinforce new policies and procedures towards sustainable development projects. Finding adequate land for any new business or development activity is a key factor considered in sustainable theories. Big projects involve numerous factors, and this makes land selection as a complex activity; thus, it is not easy to find the best suitable land parcel for development projects. Therefore, this chapter highlights the significance and effectiveness of GIS and MCDM in resolving various land suitability issues. The integration of GIS and various MCDM approaches is successfully seen in resolving land suitability problems in the world.